(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2023)
In order to study the needs and requirements for everyday clothes and to eliminate the problems arising in them, the analysis of fabrics was carried out on the basis of modern equipment. Fabrics resistant to deformation were chosen for everyday wear